"TAX AMNESTY" UPAYA PEMERINTAH MENINGKATKAN KEPATUHAN WAJIB PAJAK - andreas rudiwantoro (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2017)
AbstactIn the Tax Amnesty Constitution, it is confirmed that tax amnesty is an act of abolition towards outstanding taxes debt, which will not be fined for taxation administration and convicted of crime in the taxation field by unveiling wealth which has not been reported (either declared or repatriated) in the annual tax report (SPT) of the previous year and paying retribution as have been regulated in the particular constitution.The government as the authorities put a serious attention towards the success of this tax amnesty policy, which is hoped to give a positive impact towards national economy and development. Various socializations, counselings, seminars, and discussions have been held in the entire nation to support this policy. Tax amnesty has positive goals, which in short term, this will generate additional income from the retribution funds paid by taxpayers who join this program, and for the following years, this policy will create obedience of the taxpayers in paying their outstanding taxes.Keywords: tax amnesty, compensation, declaration, repatriation, taxpayers and compplience of taxpayers. Abstrak Dalam UU Pengampunan Pajak atau Tax Amnesty ditegaskan bahwa pengampunan pajak adalah penghapusan pajak yang seharusnya terutang, tidak dikenai sanksi administrasi perpajakan dan sanksi pidana dibidang perpajakan dengan cara mengungkapkan harta yang belum disampaikan (deklarasi dan repatriasi) dalam laporan SPT tahun sebelumnya dan membayar uang tebusan sesuai yang diatur dalam UU tersebut.Pemerintah selaku pemegang kekuasaan menaruh perhatian cukup serius terhadap kesuksesan kebijakan tax amnesty / pengampunan pajak yang diharapkan dapat berdampak positif terhadap perekonomian dan pembangunan nasional. Kegiatan sosialisasi, penyuluhan, seminar dan diskusi telah dilakukan diseluruh pelosok negeri. Pengampunan pajak atau tax amnesti memiliki tujuan positif dimana dalam jangka pendek akan menghasilkan tambahan penerimaan negara dari uang tebusan yang dibayarkan wajib pajak yang mengikuti program pengampunan pajak dan untuk tahun tahun kedepan akan menciptakan kepatuhan wajib pajak dalam membayar pajak terhutangnya. Kata kunci: Pengampunan pajak, uang tebusan, deklarasi, repatriasi, wajib pajak dan kepatuhan wajib pajak.